Resource Allocation Influence on Application Performance in Sliced Testbeds - Moreira, Rodrigo; Moreira, Larissa F. Rodrigues; Carvalho, Tereza C.; Silva, Flávio de Oliveira (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF); 2024: Anais do XV Workshop de Pesquisa Experimental da Internet do FuturoDO - 10.5753/wpeif.2024.2095, 2024)
Modern network architectures have shaped market segments, governments, and communities with intelligent and pervasive applications. Ongoing digital transformation through technologies such as softwarization, network slicing, and AI drives this evolution, along with research into Beyond 5G (B5G) and 6G architectures. Network slices require seamless management, observability, and intelligent-native resource allocation, considering user satisfaction, cost efficiency, security, and energy. Slicing orchestration architectures have been extensively studied to accommodate these requirements, particularly in resource allocation for network slices. This study explored the observability of resource allocation regarding network slice performance in two nationwide testbeds. We examined their allocation effects on slicing connectivity latency using a partial factorial experimental method with Central Processing Unit (CPU) and memory combinations. The results reveal different resource impacts across the testbeds, indicating a non-uniform influence on the CPU and memory within the same network slice.